Desvenlafaxine Versus Placebo in the Treatment of Children and Adolescents with Major Depressive Disorder - Atkinson, Sarah (J Child Adolesc Psychopharmacol, 2018)
Objective: To evaluate the short-term efficacy and safety of desvenlafaxine versus placebo in the treatment of children and adolescents with major depressive disorder (MDD). Methods: Outpatient children (7–11 years) and adolescents (12–17 years) who met DSM-IV-TR criteria for MDD and had screening and baseline Children's Depression Rating Scale-Revised (CDRS-R) total scores >40 were randomly assigned to 8 weeks of treatment with placebo, low exposure desvenlafaxine (20, 30, or 35 mg/day based on baseline weight), or higher exposure desvenlafaxine (25, 35, or 50 mg/day based on baseline weight). The primary efficacy endpoint was change from baseline in CDRS-R total score at week 8, analyzed using a mixed-effects model for repeated measures. Secondary efficacy assessments included Clinical Global Impressions-Severity and Clinical Global Impressions-Improvement scales. Safety assessments included adverse events and the Columbia-Suicide Severity Rating Scale. Results: The safety population included 363 patients (children, n = 109; adolescents, n = 254). No statistical separation from placebo was observed for either desvenlafaxine group for CDRS-R total score or for any secondary efficacy endpoint. At week 8, adjusted mean (standard error) changes from baseline in CDRS-R total score for the desvenlafaxine low exposure, desvenlafaxine high exposure, and placebo groups were −23.7 (1.1), −24.4 (1.1), and −22.9 (1.1), respectively. The incidence of adverse events was similar among groups. Conclusion: Low and high exposure desvenlafaxine groups did not demonstrate efficacy for the treatment of MDD in children and adolescents in this double-blind, placebo-controlled trial. Desvenlafaxine (20–50 mg/day) was generally safe and well tolerated with no new safety signals identified in pediatric patients with MDD in this study.